Aplikasi Scanner QR Code Berbasis Android Sebagai Alat Identifikasi Produk UKM Majalengka - Topan Trianto; Rahmayani Rahmayani (Masoem University, 2021)
Along with the construction of infrastructure in the form of toll roads and the International Airport in Majalengka, various products produced by SMEs in Majalengka must be immediately known by the market. Therefore, an application was made android-based QR code scanner application has been developed as a tool to identify original products from Majalengka. This research aims to help introduce UKM products and provide information about the identity of UKM products to the market quickly, practically and sustainably. The method used consists of collecting data and developing a system based on RUP (Rational Unified Process) with UML (Unified Modeling Language) as a development tool. This research resulted in a scanner application called 'Majalengka Product Index' which can be installed and operated directly by the market via Android devices. The result of scanning the QR code is in the form of an image display and a description of the product you want to know. The results of the application usability test survey from 65 respondents, obtained a total final score of 197.17 and included in the score range 155.51 - 203.75 with the